Effect of feeding on the pharmacokinetics of vilazodone in dogs. (August 2019) - Sartini, Irene; Gbylik-Sikorska, Małgorzata; Łebkowska-Wieruszewska, Beata; Gajda, Anna; Lisowski, Andrzej; Kowalski, Cezary J.; Posyniak, Andrzej; Poapolathep, Amnart; Giorgi, Mario
Abstract: Vilazodone (VLZ) is a drug approved for the treatment of major depressive disorder in humans but no data are available for dogs. The present study aimed to evaluate the pharmacokinetics of a single oral 40 mg dose of VLZ in healthy Labrador dogs ( n  = 6) in fasted and fed conditions. Dogs were randomly divided in two ( n  = 3) groups in a cross-over study design (2 × 2). Group I was administered with VLZ at 40 mg/dog after fasting over-night. Group II was fed prior to and after administration of the same dose. A two-week wash-out period was observed. Plasma samples collected underwent LC-MS/MS analysis. VLZ concentrations were quantified in dogs' plasma in two different windows of time: 30 min to 10 h for the fasted group and 4 h to 35 h for the fed group. The values for t1/2λz were statistically different between the groups (fed, 4.6 ± 1.1 h vs fasted, 1.7 ± 0.2 h). Tmax drastically changed between the groups (fed, 10 h vs fasted, 1.5 h), while Cmax did not significantly vary (fed, 39.4 ± 5.6 ng/mL vs fasted, 38.7 ± 4.8 ng/mL). The AUC value was always statistically higher in the fed group. As a result, the average relative oral fasted bioavailability of VLZ was low, 28.8 ± 6.1%. In conclusion, feeding can affect the pharmacokinetics of VLZ in the dog. Highlights: The fed status increased Tmax and AUC but did not change Cmax of VLZ in dogs. The relative oral bioavailability of VLZ in fasted dogs was low (28.8%). The oral administration of the human dose produced an AUC in dogs that is around 14% of that in humans.